Rancang Bangun dan Implementasi Robot Line Follower Automatic Guide Vehicle (AGV) untuk Pengangkutan Barang Berbasis Arduino - Nur Insani, Fadlur; Syamsudin, Mariana; Riyanto, Agus; Mardianto, Eko; Rianda, Rianda (Electrical Network Systems and Sources, 2024)
In the era of digitalization 4.0, technology plays a crucial role in enhancing efficiency across various industrial sectors. This research proposes the design and development of a Robot Line Follower AGV for automated goods transportation. This robot utilizes an Arduino Uno microcontroller as the control center and is equipped with four primary sensors: IR TCRT5000, Ultrasonic HC-SR04, Load Cell, and TCS3200 Color Sensor. Output indicators, including a Buzzer and LED, provide operational feedback, while a DC motor is controlled by a PID algorithm to ensure accurate movement along the path. The development of this system is expected to improve the efficiency of goods transportation processes while fostering innovation in the industrial and creative economy sectors.